Reinforcement of Piles in Landslides at KM. 619+900 - Ardika, Jumelia -; Yunita, Halida; Sungkar, Munira; Akmal, Abdiel Khaleil; Al-Huda, Nafisah; Munir, Badrul; Elmira, Fara Qamara; Fachri, Fachri (invotek, 2024)
Landslides are events that can cause both moral and non-moral losses, one of which is the damage to the Subulussalam–Lipat Kajang Road section at KM. 619+900, resulting in restricted movement and disrupted activities of the local community. This could be due to factors such as rainfall or groundwater levels. Therefore, this research was conducted with the aim of addressing the existing problems by providing appropriate and effective solutions to the landslides caused. This research uses secondary data and primary data in analyzing slope stability. The initial conditions and the slope conditions following sheet pile reinforcement are used this analysis. An application called Plaxis is required in order to examine the slope stability. This study produced a safety factor value of 1.104 under existing conditions, and after being reinforced with sheet piles, the safety factor value increased to 1.502. However, if the slope in the existing condition is subjected to an earthquake load, it will obtain a very low safety factor value of 1.044, and this requires strengthening with sheet piles and anchors to increase the safety factor value, ensuring that the slope is in a stable condition. This research provides one of the much-needed alternatives in addressing landslide issues, especially in the fields of construction and geotechnical engineering. The findings of this research can serve as a reference or guideline in the civil engineering planning process, particularly in the use of reinforcement systems such as sheet piles (retaining walls) and anchors as effective solutions.